Comparison of Preschooler Verbal and Graphic Symbol Production Across Different Syntactic Structures - Savaldi-Harussi, Gat; Fostick, Leah (Frontiers in Psychology, 2021)
The present study focuses on the impact of graphic symbols used in Augmentative and Alternative Communication (AAC) on clause construction. It is not yet well-understood to what extent communication produced via graphic symbols differs from verbal production. This study attempts shed light on the impact of the graphic symbol modality on message construction beyond individual differences, language knowledge, and language-specific patterns by providing a direct comparison between children’s verbal and graphic symbol production. Nineteen typically-developing Hebrew-speaking children aged 4-5 years were presented with 16 short videos of actions and were asked to express what they saw verbally and by choosing among graphic symbols displayed on an iPad communication board. The 570 clauses produced by the children were coded and analyzed. A significant difference was found in favor of verbal speech across different syntactic structures in terms of utilization of the target lexicon, syntactic complexity, and expected target word order. These results are consistent with the existing literature for English. Implications for AAC practices are discussed, highlighting the notion that using graphic symbols to represent spoken language may not reflect actual linguistic knowledge and that adequate, explicit instruction is necessary for graphic representation of more complex linguistic structures.